DEFINING THE RELEVANT OUTCOME MEASURES IN MEDICAL DEVICE ASSESSMENTS: AN ANALYSIS OF THE DEFINITION PROCESS IN HEALTH TECHNOLOGY ASSESSMENT. (31st May 2017) - Jacobs, Esther; Antoine, Sunya-Lee; Prediger, Barbara; Neugebauer, Edmund; Eikermann, Michaela
Abstract : Background: Defining relevant outcome measures for clinical trials on medical devices (MD) is complex, as there is a large variety of potentially relevant outcomes. The chosen outcomes vary widely across clinical trials making the assessment in evidence syntheses very challenging. The objective is to provide an overview on the current common procedures of health technology assessment (HTA) institutions in defining outcome measures in MD trials. Methods: In 2012–14, the Web pages of 126 institutions involved in HTA were searched for methodological manuals written in English or German that describe methods for the predefinition process of outcome measures. Additionally, the institutions were contacted by email. Relevant information was extracted. All process steps were performed independently by two reviewers. Results: Twenty-four manuals and ten responses from the email request were included in the analysis. Overall, 88.5 percent of the institutions describe the type of outcomes that should be considered in detail and 84.6 percent agree that the main focus should be on patient relevant outcomes. Specifically related to MD, information could be obtained in 26 percent of the included manuals and email responses. Eleven percent of the institutions report a particular consideration of MD related outcomes. Conclusions: This detailed analysis on common procedures of HTA institutions in the context of defining relevant outcome measures for the assessment of MD shows that standardized procedures for MD from the perspective of HTA institutions are not widespread. This leads to the question if a homogenous approach should be implemented in the field of HTA on MD.